Bush pepper cultivation – A remunerative hobby for rural women - Thomas, Manju; Sam, Binu John (Indian Horticulture, 2022)
ICAR-KVK, Mitraniketan has been promoting bush pepper cultivation in homesteads as a remunerative hobby for rural women since 2018. Trivandrum is an urban district in the state of Kerala, where cultivable land is fast getting converted for construction purposes and the labour charges are soaring. Against this back drop, bush pepper was introduced as a new generation spice crop which requires neither much space nor much labour for its successful cultivation.